Planet Hunters TESS III: two transiting planets around the bright G dwarf HD 152843. Issue 2 (12th May 2021) - Eisner, N L; Nicholson, B A; Barragán, O; Aigrain, S; Lintott, C; Kaye, L; Klein, B; Miller, G; Taylor, J; Zicher, N; Buchhave, L A; Caldwell, D A; et al.
ABSTRACT: We report on the discovery and validation of a two-planet system around a bright ( V = 8.85 mag) early G dwarf (1.43 R⊙, 1.15 M⊙, TOI 2319) using data from NASA's Transiting Exoplanet Survey Satellite ( TESS ). Three transit events from two planets were detected by citizen scientists in the month-long TESS light curve (sector 25), as part of the Planet Hunters TESS project. Modelling of the transits yields an orbital period of 11.6264 _ - 0.0025 ^ + 0.0022 d and radius of 3.41 _ - 0.12 ^ + 0.14 R⊕ for the inner planet, and a period in the range 19.26–35 d and a radius of 5.83 _ - 0.14 ^ + 0.14 R⊕ for the outer planet, which was only seen to transit once. Each signal was independently statistically validated, taking into consideration the TESS light curve as well as the ground-based spectroscopic follow-up observations. Radial velocities from HARPS-N and EXPRES yield a tentative detection of planet b, whose mass we estimate to be 11.56 _ - 6.14 ^ + 6.58 M⊕, and allow us to place an upper limit of 27.5 M⊕ (99 per cent confidence) on the mass of planet c. Due to the brightness of the host star and the strong likelihood of an extended H/He atmosphere on both planets, this system offers excellent prospects for atmospheric characterization and comparative planetology.